(untitled) (Journal of the College of Basic Education, 2022)
Jazz Age is a name given to an age in America in the early 20th century. This age is characterized by improvisation and strong rhythms of popular music which was first played by Negro groups southern U.S.A. Fitzgerald portrays the 1920s as an era of decayed social and moral values, evidenced in its overarching cynicism, greed and empty pursuit of pleasure.